Competitive biosorption of ortho-cresol, phenol, chlorophenol and chromium(VI) from aqueous solution by a bacterial biofilm supported on granular activated carbon - Quintelas, C. (2006)
A biofilm of Arthrobacter viscosus supported on granular activated carbon was used to remove chromium and organic compounds (chlorophenol, phenol and o-cresol) from aqueous solutions. The compounds were studied as single solutes and in different combinations between them and Cr(VI). Optimum Cr(VI) adsorption was observed at a phenol concentration of 100 mg/l and at an initial concentration of the metal of 60 mg/l. The maximum values of biosorption of organic compounds were 9.94 mg/g for phenol, 9.70 mg/g for chlorophenol and 13.99 mg/g for o-cresol. In terms of removal percentage, after 15 h of experiment, the affinity order was as follows: phenol > chlorophenol > o-cresol > chromium(VI).